Kandungan Energi Bruto, Energi Tercerna dan Energi Metabolis Pakan Cair Fermentasi Berbahan Biji Asam Utuh pada Babi Grower: Gross Energy Content and Prediction of Digestible Energy and Metabolic Energy of Tamarind Seed Liquid Feed Fermentation of Pig Grower - Redempta Wea; Bernadete Barek Koten; Christian Abimayu Morelaka (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Tamarind seeds have a high energy content but have limited use for pigs because the seed coat is tough and contains anti-nutrient tannins. Therefore, liquid feed fermentation technology is carried out. The aim of this research was to assess the gross energy, digestible energy, and metabolic energy content of liquid feed fermentation (Lff) with different fermentation times in growing pigs. The research materials were whole tamarind seeds, bran, corn, meat and bone meal, and soybean meal. The study used a completely randomized design and consisted of 5 treatments and 5 replications. Treatment = Lf0: Lff time 0 days; Lf1: Lff for 7 days, Lf2: Lff for 14 days, Lf3: Lff for 21days, Lf4: Lff for 28 days fermentation. The research variables were the energy content of the ration and the prediction of digestible energy and metabolic energy value. Data were analyzed using analysis of variance and Duncan's advanced test. The results showed that the Lff with different fermentation time had a significant effect (P <0,05) on gross energy, digestible energy, and metabolic energy value. The best value of energy is Lff for 21 days. It was concluded that the time for fermentation of liquid feed made from tamarind seeds which can produce good energy content, digestibility, and metabolic energy is 21 days.